The impact of activity ratio towards firm’s performance of the listed healthcare companies in Singapore Exchange (SGX) / Nur Farahany Farrisha Sukri …[et al.] - Sukri, Nur Farahany Farrisha; Mohamad Shahrizad, Hariz Izzudin; Shahrol Nizam, Najah; Nik Mohd Khairi, Nik Afiqah Farhah; Izuddin, Nurizwa Baizura (2023)
This research determines the impacts of activity ratio towards company’s performance in healthcare industries that are listed on the Singapore Stock Exchange. Five independent variables used in this study are Total Assets Turnover (TATO), Fixed Assets Turnover (FATO), Working Capital Turnover (WCTO), Receivables Turnover (RTO), Inventory Turnover (ITO). The dependent variable used in this study is a company’s financial performance which is measured by Return on Assets (ROA) and Net Profit Margin (NPM). A total of 25 companies with complete data from the healthcare industries have been chosen. This study used secondary data derived from the financial statements over 6 years from 2017 – 2021. The data has been analyzed by using regression analysis in Statistical Package for Social Sciences (SPSS). The findings revealed that TATO, ITO, FATO have no impact towards ROA while RTO and WCTO have impact towards ROA. However, all variables have an impact on a company’s performance that is measured by NPM. The paper recommends that companies pay attention to asset management and profitability ratios to improve their performance, and investors should consider these factors when investing in healthcare companies.